2020
DOI: 10.1136/jitc-2020-000627
|View full text |Cite
|
Sign up to set email alerts
|

Dose escalation phase 1 study of radiotherapy in combination with anti-cytotoxic-T-lymphocyte-associated antigen 4 monoclonal antibody ipilimumab in patients with metastatic melanoma

Abstract: BackgroundA synergy between radiotherapy and anti-cytotoxic-T-lymphocyte-associated antigen 4 (anti-CTLA-4) monoclonal antibody has been demonstrated preclinically. The Mel-Ipi-Rx phase 1 study aimed to determine the maximum tolerated dose (MTD) and safety profile of radiotherapy combined with ipilimumab in patients with metastatic melanoma.Patients and methodsA 3+3 dose escalation design was used with 9, 15, 18 and 24 Gy dose of radiotherapy at week 4 combined with 10 mg/kg ipilimumab every 3 weeks for four d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 32 publications
(37 reference statements)
1
10
0
Order By: Relevance
“…There was no association seen between CD8 T cell infiltration or PD-L1 expression and response, however RT-induced IFNb secretion and sustained TCR clonal expansion was associated with an abscopal response (29). Conversely, a recent phase I study evaluating RT in combination with anti-CTLA-4 in metastatic melanoma showed CD8 infiltration to be significantly correlated with PFS (NCT01557114) (110). McBride et al also evaluated the mechanics of the abscopal effect in a phase II study of Nivolumab with or without SBRT in metastatic HNSCC.…”
Section: Clinical Translationmentioning
confidence: 99%
“…There was no association seen between CD8 T cell infiltration or PD-L1 expression and response, however RT-induced IFNb secretion and sustained TCR clonal expansion was associated with an abscopal response (29). Conversely, a recent phase I study evaluating RT in combination with anti-CTLA-4 in metastatic melanoma showed CD8 infiltration to be significantly correlated with PFS (NCT01557114) (110). McBride et al also evaluated the mechanics of the abscopal effect in a phase II study of Nivolumab with or without SBRT in metastatic HNSCC.…”
Section: Clinical Translationmentioning
confidence: 99%
“…Co-stimulatory [77] 9 Gy [77] IO given before (week 1), concurrently (week 4) and after (weeks 7 and 10) RT [77] NSCLC [38] NCT02221739; Interventional Phase 1-2; n: 39 Increased level of serum IFN-β; changes in T cell clones; systemic anti-tumor response T cell-mediated [38] 5 × 6 Gy, 3 × 9.5 Gy [38] IO given concurrently and after RT (on day 22, 43, 64 of the treatment regimen) [38] PD-1/PD-L1 (Programmed Death/Ligand-1)…”
Section: Ox40 (Or Cd134)mentioning
confidence: 99%
“…This pivotal trial led to Ipilimumab being the first immune checkpoint blockade therapy approved by the Food and Drug Administration (FDA) in 2011 for patients with advanced melanoma, a disease stage for which there was no previous standard of care therapy that prolonged survival. Since then, αCTLA-4 blockade has been examined extensively in pre-clinical studies and clinical trials as a single agent and in combination with chemotherapy [ 288 , 289 , 290 ], radiotherapy [ 291 , 292 , 293 ], cancer vaccination [ 294 ], and other immunotherapies [ 295 , 296 , 297 ]. However, it is the combination of αPD-1/αCTLA-4 blockade that has demonstrated the greatest therapeutic efficacy in the clinic, with ipilimumab (αCTLA-4) and nivolumab (αPD-1) approved for treatment of patients with advanced solid tumours ( Table 2 ).…”
Section: Inhibitory Receptorsmentioning
confidence: 99%